Fostering Students’ English Academic Performance Through Innovative Experiential Learning at Secondary Level - Zahro, Siti Nuruz; Jamilah, Jamilah (Indonesian Journal of Advanced Research, 2024)
This study explores the use of innovative experiential learning as an alternative to the lecture method, which often leaves students silent and disengaged. It aims to improve students' English academic performance and examine the role of social-emotional competence in linking experiential learning to academic outcomes. Conducted as Classroom Action Research (CAR) in an eleventh grade, the study followed two cycles of planning, acting, observing, and reflecting. Results show that experiential learning enhances English performance by fostering active participation, critical thinking, communication, and motivation through real-world applications. Social-emotional competence significantly mediates these improvements, supporting the value of interactive and practical teaching methods.